2014
DOI: 10.1002/jsfa.7020
|View full text |Cite
|
Sign up to set email alerts
|

Lipoic acid mitigates oxidative stress and recovers metabolic distortions in salt‐stressed wheat seedlings by modulating ion homeostasis, the osmo‐regulator level and antioxidant system

Abstract: LA reduced salinity-induced oxidative damage and thus contributed to the growth and development of plants in saline soils by modulating ion homeostasis between plant and soil as well as in osmo-regulator content and antioxidant system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 52 publications
(59 reference statements)
5
22
1
Order By: Relevance
“…In addition, our findings show that the improvement in water status following the exogenous application of ALA may be the result of the alleviation of the detrimental effects of osmotic stress. Similar to our findings, Görcek and Erdal [9] reported that exogenous ALA treatment mitigated the salt-induced decrease in water status and, hence, contributed by increasing the leaf surface area. In addition, the authors indicated that enhancement of the water status and leaf surface area due to foliar application of ALA was due to its modulating role in ion homeostasis, osmotic regulation and the antioxidant system.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, our findings show that the improvement in water status following the exogenous application of ALA may be the result of the alleviation of the detrimental effects of osmotic stress. Similar to our findings, Görcek and Erdal [9] reported that exogenous ALA treatment mitigated the salt-induced decrease in water status and, hence, contributed by increasing the leaf surface area. In addition, the authors indicated that enhancement of the water status and leaf surface area due to foliar application of ALA was due to its modulating role in ion homeostasis, osmotic regulation and the antioxidant system.…”
Section: Discussionsupporting
confidence: 92%
“…The reduction in H 2 O 2 content after ALA application may be due to its ability to scavenge ROS, as antioxidant enzymes. This correlates with the findings of Gorcek and Erdal [9] who observed that ALA significantly reduced H 2 O 2 and superoxide contents and contributed to the response to oxidative damage and metabolic distortions in salt-stressed wheat seedlings. Likewise, in another study, it was shown that ALA can have protective and antimutagenic effects against oxidants (particularly H 2 O 2 ) in yeast cells via its antioxidant activity [28].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Some data showed a high level of free proline accumulation in the salt-tolerant cultivar than in the salt-sensitive cultivar under salt stress (Misra and Gupta, 2005; Khan et al, 2009). By contrast, some studies demonstrated that the salt-sensitive cultivar accumulates more proline than salt-tolerant cultivar under salt stress (Lutts et al, 1999; Claussen, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chlorophyll content was measured by the spectrophotometric method . Absorbance was measured at wavelengths of 645 and 663 nm, and 80% acetone aqueous solution was used as a reference.…”
Section: Methodsmentioning
confidence: 99%